Methotrexate resistance in relation to treatment outcome in childhood acute lymphoblastic leukemia - Wojtuszkiewicz, Anna (J Hematol Oncol, 2015)
BACKGROUND: Methotrexate (MTX) eradicates leukemic cells by disrupting de novo nucleotide biosynthesis and DNA replication, resulting in cell death. Since its introduction in 1947, MTX-containing chemotherapeutic regimens have proven instrumental in achieving curative effects in acute lymphoblastic leukemia (ALL). However, drug resistance phenomena pose major obstacles to efficacious ALL chemotherapy. Moreover, clinically relevant molecular mechanisms underlying chemoresistance remain largely obscure. Several alterations in MTX metabolism, leading to impaired accumulation of this cytotoxic agent in tumor cells, have been classified as determinants of MTX resistance. However, the relation between MTX resistance and long-term clinical outcome of ALL has not been shown previously. METHODS: We have collected clinical data for 235 childhood ALL patients, for whom samples taken at the time of diagnosis were also broadly characterized with respect to MTX resistance. This included measurement of concentrations of MTX polyglutamates in leukemic cells, mRNA expression of enzymes involved in MTX metabolism (FPGS, FPGH, RFC, DHFR, and TS), MTX sensitivity as determined by the TS inhibition assay, and FPGS activity. RESULTS: Herein we demonstrate that higher accumulation of long-chain polyglutamates of MTX is strongly associated with better overall (10-year OS: 90.6 vs 64.1 %, P = 0.008) and event-free survival (10-year EFS: 81.2 vs 57.6 %, P = 0.029) of ALL patients. In addition, we assessed both the association of several MTX resistance-related parameters determined in vitro with treatment outcome as well as clinical characteristics of pediatric ALL patients treated with MTX-containing combination chemotherapy. High MTX sensitivity was associated with DNA hyperdiploid ALL (P < 0.001), which was linked with increased MTX accumulation (P = 0.03) and elevated reduced folate carrier (RFC) expression (P = 0.049) in this subset of ALL patients. TEL-AML1 fusion was associated with increased MTX resistance (P = 0.023). Moreover, a low accumulation of MTX polyglutamates was observed in MLL-rearranged and TEL-AML1 rearranged ALL (P < 0.05). CONCLUSIONS: These findings emphasize the central role of MTX in ALL treatment thereby expanding our understanding of the molecular basis of clinical differences in treatment response between ALL individuals. In particular, the identification of patients that are potentially resistant to MTX at diagnosis may allow for tailoring novel treatment strategies to individual leukemia patients. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13045-015-0158-9) contains supplementary material, which is available to authorized users.